Naringenin induces ferroptosis in osteosarcoma cells through the STAT3-MGST2 signaling pathway - Yingang Li; Xizhuang Bai (Journal of Bone Oncology)
Osteosarcoma is a common malignant tumor found in adolescents, characterized by a high metastatic potential and poor prognosis, but it is sensitive to radiotherapy and chemotherapy. Ferroptosis is a novel form of regulated cell death induced by excessive iron accumulation, leading to lipid peroxidation that results in cellular dysfunction and death. Naringenin is a flavonoid known for its anti-cancer properties, yet its role in osteosarcoma has not been thoroughly studied. In this study, we found that naringenin significantly reduced the viability of osteosarcoma cells while increasing the accumulation of reactive oxygen species (ROS), iron overload, and the excessive expression of malondialdehyde (MDA). Bioinformatics analysis revealed that microsomal glutathione S-transferase 2 (MGST2) is highly expressed in osteosarcoma cells. Silencing MGST2 decreased the proliferation, migration, and invasion of these cells and enhanced their sensitivity to ferroptosis. Mechanistically, signal transducer and activator of transcription 3 (STAT3) binds to the MGST2 promoter, promoting its transcription. Naringenin inhibits STAT3, blocking the expression of MGST2, while the STAT3 agonist Colivelin reverses this effect. In vivo experiments further confirmed that naringenin inhibited tumor growth in subcutaneous xenograft models and exhibited good biosafety. In summary, our study demonstrates that naringenin induces ferroptosis in osteosarcoma cells through the STAT3-MGST2 signaling pathway, providing a promising strategy for osteosarcoma treatment.